PENGARUH STRATEGI PEMBELAJARAN INKUIRI TERBIMBING BERBANTUAN LABORATORIUM VIRTUAL PADA PEMBELAJARAN TEMATIK TERHADAP KEMAMPUAN BERPIKIR KRITIS SISWA SEKOLAH DASAR - Iis Lestari; Dedi Kuswandi; Dwi Agus Sudjimat (Jurnal Penelitian Pendidikan IPA, 2023)
Technological developments in the world of education are very rapid, requiring education to continue to have innovation and renewal in learning approaches to be able to produce generations or highly competitive human resources who are able to have critical thinking skills. The purpose of this research is to determine the differences in critical thinking abilities between students who are taught using a guided inquiry learning strategy assisted by a virtual laboratory and those who are taught using a guided inquiry strategy without the assistance of a virtual laboratory in thematic learning in class V elementary school. This type of research is quasi-experimental, while the research design used is nonequivalent control group design. The sampling technique uses nonprobability sampling with a saturated sampling technique. Meanwhile, the instrument in this research is a test. The results of the research through hypothesis testing using the t test with a significance level of 5%, show that the > (3,283 > 2,712) and the significant value shows sig < 0.05 (0.002 < 0.05), then is rejected and is accepted, so it can be concluded that there is differences in critical thinking abilities between students who were taught using guided inquiry learning strategies assisted by virtual laboratories and those taught using guided inquiry strategies without virtual laboratory assistance in thematic learning in class V of elementary schools